SXT/R391 Integrative and Conjugative Elements (ICEs) Encode a Novel ‘Trap-Door’ Strategy for Mobile Element Escape - Ryan, Michael P. (Front Microbiol, 2016)
Integrative conjugative elements (ICEs) are a class of bacterial mobile elements that have the ability to mediate their own integration, excision, and transfer from one host genome to another by a mechanism of site-specific recombination, self-circularisation, and conjugative transfer. Members of the SXT/R391 ICE family of enterobacterial mobile genetic elements display an unusual UV-inducible sensitization function which results in stress induced killing of bacterial cells harboring the ICE. This sensitization has been shown to be associated with a stress induced overexpression of a mobile element encoded conjugative transfer gene, orf43, a traV homolog. This results in cell lysis and release of a circular form of the ICE. Induction of this novel system may allow transfer of an ICE, enhancing its survival potential under conditions not conducive to conjugative transfer.